A Comparative Study of the Impact of Globalization on Iran's Social Development in the Two Governments of Khatami and Ahmadinejad - Farzaneh Seifoori; Seyed Amir Masoud Shahram Nia; Abbas Hatami; Seyed Javad Emam Jomeh Zadeh (توسعه اجتماعی)
The globalization and the development of the independent and interdependent discourses have been less considered in comparison to each other. The present study is influenced by the impact of globalization on development. It has chosen Roland Robertson from among the theorists in this field. This paper, with an emphasis on the social aspects of globalization, aims to compare the impact of globalization on the social development of the Islamic Republic of Iran in two administrations led by Khatami and Ahmadinejad from 1997 to 2013. Thus, the independent variable of this study will be the globalization and variability of the social development of Iran in these two administrations. In terms of the theoretical foundations in this research, the patterns of generalization of political development and social development are selected. The research hypothesis was looked at with regard to the world-leading statistics on social development in both administrations, Khatami's approach based on reform and global reform, and Ahmadinejad's approach based on indigenous and local criteria. The research method is comparative. Studies in the present paper show that the trend of globalization in both administrations has contributed to the growth and development of social aspects, and has greased the wheels for a different continuation of this process in Iran as compared to other countries.